Cardiovascular Disease and High-Mobility Group Box 1—Is a New Inflammatory Killer in Town?. (July 2013) - Cirillo, Plinio; Giallauria, Francesco; Palma, Vito Di; Maresca, Fabio; Ziviello, Francesca; Bevilacqua, Michele; Vigorito, Carlo; Trimarco, Bruno
High-mobility group box 1 (HMGB-1) is a nuclear protein physiologically involved in the maintaining of DNA structure in the nucleus. When tissue damage occurs, necrotic cells as well as inflammatory cells, once activated, release this protein in circulating blood, where it seems to exert a direct proinflammatory action. Thus, HMGB-1 might be involved in the pathophysiology of several diseases, including cardiovascular disease. However, the experimental evidence has not yet clarified its cardiovascular role which is still debated. Specifically, it is still not completely resolved whether HMGB-1 plays a protective or detrimental role on cardiovascular function. In this review, we consider the role of HMGB-1 in pathological conditions and comment on the role of this protein in the cardiovascular disease.